Results of hydrocephalus surgical treatment, caused by perinatal brain injury, at children - Orlov, Yu. A.; Marushchenko, L. L.; Protsenko, I. P. (Ukrainian Neurosurgical Journal, 2009)
The surgical treatment results of 237 children with progressive hydrocephalus, caused by perinatal brain injury, were analyzed. The rational surgical tactics at progressive hydrocephalus was developed and applied that provided decrease of malfunctions frequency of the shunt systems from 21,9 to 9,4%, infectious-inflammatory complications — from 18,2 to 10,7%, mortality — from 8,2 to 1,5%. The program complex for prediction of hydrocephalus outcomes, caused by perinatal brain injury, was offered and quantitative evaluation of prognostic factors was made.